Nitrogen additions stimulate litter humification in a subtropical forest, southwestern China. Issue 1 (December 2018) - Liu, Qun; Zhuang, Liyan; Ni, Xiangyin; You, Chengming; Yang, Wanqin; Wu, Fuzhong; Tan, Bo; Yue, Kai; Liu, Yang; Zhang, Li; Xu, Zhenfeng
Abstract Despite the importance of nitrogen (N) deposition for soil biogeochemical cycle, how N addition affects the accumulation of humic substances in decomposing litter still remains poorly understood. A litterbag experiment was conducted to assess the potential effects of N addition (0 kg·N·ha−1 ·year−1, 20 kg·N·ha−1 ·year−1 and 40 kg·N·ha−1 ·year−1 ) on mass remaining and humification of two leaf litter (Michelia wilsonii andCamptotheca acuminata ) in a subtropical forest of southwestern China. After one year of decomposition, litter mass was lost by 38.1–46.5% forM .wilsonii and 61.7–74.5% forC .acuminata, respectively. Humic substances were declined by 12.1–23.8% inM .wilsonii and 29.1–35.5% inC .acuminata, respectively. Nitrogen additions tended to reduce mass loss over the experimental period. Moreover, N additions did not affect the concentrations of humic substances and humic acid in the early stage but often increased them in the late stage. The effect of N addition on the accumulation of humic substances was stronger forC .acuminate litter than inM .wilsonii litter. Litter N and P contents showed positive correlations with concentrations of humic substances and fulvic acid. Our results suggest that both litter quality and season-driven environmental changes interactively mediate N impacts on litter humification. Such findings have important implications for carbon sequestration via litter humification in the subtropical forest ecosystems experiencing significant N deposition.